A review of polystyrene bead manipulation by dielectrophoresis. Issue 9 (8th February 2019) - Chen, Qiaoying; Yuan, Yong J.
Abstract : Exploitation of the intrinsic electrical properties of particles has recently emerged as an appealing approach for trapping and separating various scaled particles. Abstract : Exploitation of the intrinsic electrical properties of particles has recently emerged as an appealing approach for trapping and separating various scaled particles. Initiative particle manipulation by dielectrophoresis (DEP) showed remarkable advantages including high speed, ease of handling, high precision and being label-free. Herein, we provide a general overview of the manipulation of polystyrene (PS) beads and related particles via DEP; especially, the wide applications of these manipulated PS beads in the quantitative evaluation of device performance for model validation and standardization have been discussed. The motion and polarizability of the PS beads induced by DEP were analyzed and classified into two categories as positive and negative DEP within the time and space domains. The DEP techniques used for bioparticle manipulation were demonstrated, and their applications were conducted in four fields: trapping of single-sized PS beads, separation of multiple-sized PS beads by size, separation of PS beads and non-bioparticles, and separation of PS beads and bioparticles. Finally, future perspectives on DEP-on-a-chip have been proposed to discriminate bio-targets in the network of microfluidic channels.